Validation of an inertial measurement unit for the measurement of jump count and height - MacDonald, K.; Bahr, R.; Baltich, J.; Whittaker, J. L.; Meeuwisse, W. H. (Physical Therapy in Sport, 2017)
Objectives: To validate the use of an inertial measurement unit (IMU) for the collection of total jump count and assess the validity of an IMU for the measurement of jump height against 3-D motion analysis. Design: Cross sectional validation study. Setting: 3D motion-capture laboratory and field based settings. Participants: Thirteen elite adolescent volleyball players. Independent variables: Participants performed structured drills, played a 4 set volleyball match and performed twelve counter movement jumps. Main outcome measures: Jump counts from structured drills and match play were validated against visual count from recorded video. Jump height during the counter movement jumps was validated against concurrent 3-D motion-capture data. Results: The IMU device captured more total jumps (1032) than visual inspection (977) during match play. During structured practice, device jump count sensitivity was strong (96.8%) while specificity was perfect (100%). The IMU underestimated jump height compared to 3D motion-capture with mean differences for maximal and submaximal jumps of 2.5 cm (95%CI: 1.3 to 3.8) and 4.1 cm (3.1-5.1), respectively. Conclusion: The IMU offers a valid measuring tool for jump count. Although the IMU underestimates maximal and submaximal jump height, our findings demonstrate its practical utility for field-based measurement of jump load.